2023
DOI: 10.1039/d2fd00112h
|View full text |Cite
|
Sign up to set email alerts
|

The mechanochemical excitation of crystalline LiN3

Abstract: Dynamic mechanical stress leads to rapid and transient vibrational excitation of crystalline solids, greatly altering their chemical reactivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…He found that a shock wave, especially if combined with lattice defects, causes the reduction of the Δ g , facilitating the electronic excitation that triggers decomposition. Later a process named dynamic metallization was used to explain the mechanical initiation of materials, in which shock-excited phonons cause the narrowing of the Δ g . The referred studies focused mainly on azides such as α-NaN 3 and LiN 3 …”
Section: Introductionmentioning
confidence: 99%
“…He found that a shock wave, especially if combined with lattice defects, causes the reduction of the Δ g , facilitating the electronic excitation that triggers decomposition. Later a process named dynamic metallization was used to explain the mechanical initiation of materials, in which shock-excited phonons cause the narrowing of the Δ g . The referred studies focused mainly on azides such as α-NaN 3 and LiN 3 …”
Section: Introductionmentioning
confidence: 99%
“…The mechanoexcitation of lattice vibrations, and the subsequent transfer of the energy from phonons to molecular vibrations to drive bond breaking are the main points of the model developed by A. Michalchuk et al which describes how a mechanical impact can cause a chemical transformation, such as the decomposition of energetic materials. 325–330…”
Section: Achievementsmentioning
confidence: 99%
“…[19] There is also a debate on the temperature levels in the mechanochemical reactors, which initially were thought to locally reach hundreds of degrees Celsius, but more recent studies indicate that the temperature increase in the jar is usually around a few degrees. [20][21][22][23] On the other hand, in the case of low-melting eutectic mixtures even such an increase may cause local melting of components, which justifies the question about common aspects between ball milling and melting methods. Other researchers underlined a possible participation of atmospheric moisture in facilitating cocrystal formation processes, as was the case of neat grinding of glycine and malonic acid, which form a very hygroscopic mixture, [24] as well as of spontaneous formation of caffeine, theophylline and nicotinamide cocrystals with diacid coformers, accelerated by an increase in humidity.…”
Section: Introductionmentioning
confidence: 99%
“…Amorphization was primarily observed in in‐situ powder X‐ray diffraction studies of mechanochemical formation of carbamazepine‐saccharin cocrystal in what was one of the first applications of real‐time reaction monitoring [19] . There is also a debate on the temperature levels in the mechanochemical reactors, which initially were thought to locally reach hundreds of degrees Celsius, but more recent studies indicate that the temperature increase in the jar is usually around a few degrees [20–23] . On the other hand, in the case of low‐melting eutectic mixtures even such an increase may cause local melting of components, which justifies the question about common aspects between ball milling and melting methods.…”
Section: Introductionmentioning
confidence: 99%